Performance analysis of VHSE agricultural teachers in kerala - Chhanda charana mahananda (Department of agricultural extension, college of agriculture, 2019)
The present study entitled "Performance analysis of VHSE Agricultural Teachers in Kerala" was conducted in three zones of Kerala during the academic year 2017-2019 to know the personal, socio-psychological characteristics of VHSE Teachers and organizational characteristics of VHSE, to analyze their job perception & job performance, to find out the relationship between their personal, socio-psychological characteristics and organizational characteristics of VHSE teachers with their job perception and job performance level, to identify the problems while performing their job and to suggest the effective teaching strategies of VHSE system. The study was conducted among selected 120 VHSE agricultural teachers from three zones of Kerala namely, Northern zone, Central zone and Southern zone. A structured interview schedule was prepared for data collection concerning the objectives of the study and statistical tools such as frequency, percentage, correlation and factor analysis were used. The results of the study revealed that majority of the teachers (95.83%) belonged to the middle age group category and 72.5 per cent of them were females. More than half (56%) of the teachers belonged to the rural background and 59.17 per cent of teachers were having a master's educational qualification. Furthermore, 49 per cent of the teachers have low (<6 lakhs) annual income and majority of the teachers (76%) belonged to the average (8-14 years) job experience category. However, more than half (55.83%) of teachers belonged to a low-trained (3-13 days) group, 50.83 per cent of the teachers were under medium information-seeking behaviour, 43 per cent had a high workload perspective, more than half (60.83%) of teachers had a medium achievement motivation and majority of the teachers (81.67%) were under a high scientific orientation category. It was also observed that 66.67 per cent of teachers had the most favorable attitude towards their job, 81.67 per cent and 72.50 per cent of teachers belonged to high organizational commitment and medium job involvement category respectively. It was also observed that 60 per cent of the teachers felt that their schools had a good organizational climate. The study revealed that 95 per cent of teachers had high job perception and half of the teachers (50%) had high level of job performance. The factor analysis of job perception revealed that seven factors (69.55% cumulative variance) contributing to the job perception of teachers namely; academic role, motivational role, management by objective (MBO), management information system (MIS), career counselling, readiness to support others and extra-curricular activities. Factor analysis also revealed that three factors (62.21% cumulative variance) contributing to the job performance were teaching skill, communication skill, and knowledge management. The results of the correlation analysis revealed that training and scientific orientation had a positive and significant correlation with job perception at 5% level of significance whereas workload was negatively correlated at 1% level of significance. Likewise, training and scientific orientation had a positive and significant relationship with job performance at 1% and organizational climate at 5% level of significance. Age on the other hand had a negative correlation with job performance at 5% level of significance. The major problems encountered by the teachers were low academic profile of the students (Rank 1), lack of practical oriented capacity building programmes (Rank 2), lack of opportunities for students to interact with farm communities and agripreneurs (Rank3), lack of curriculum as per the requirements of agriculture scenario of Kerala and job opportunities (Rank 4). The suggestions by teachers for the effective teaching strategies include awareness creation among public, students and parents about VHSE and its scope, conduct capacity building programmes to the teachers for upgradation of knowledge and information, providing various kinds of training, curriculum amendment, providing good infrastructural facilities and accommodation to teachers, organizing entrepreneurship development programme, regular conduct of monthly conferences and meetings, providing internet facilities and adequate library facilities. The study suggests an effective teaching strategy for VHSE teachers of Kerala through their better job perception and job performance which could be achieved by creating more awareness about their academic and motivational roles, efficient management by objective (MBO) and management information system (MIS), career counselling to students, more involvement of teachers in extracurricular activities and readiness to support each other. The study also suggesting the need for capacity building programmes to VHSE teachers to enhance their communication skill, teaching skill and knowledge management skill to improve their job performance.